Senior Nursing Students\' Skills in Patients\' Health Assessment in Zanjan University of Medical Sciences - Hossein Madani; Nasrin Bahraminejad; Korosh Amini; Abolfazl Rahimi; Ramezan Fallah (مجله ایرانی آموزش در علوم پزشکی, 2008)
Introduction: Assessing patients' health is the base of nursing process. Also finding patients' problems is necessary for designing care plan by nurses and nursing students. This study was performed to determine the proficiency level of senior nursing students in assessing patients' health in Zanjan University of Medical Sciences in the year 2005. Methods: In this descriptive cross-sectional study, all senior nursing students of Zanjan University of Medical Sciences (44 students) were studied. The data gathering tools included a questionnaire consisted of demographic data, which was filled by the samples and an observational checklist which was completed by researchers while observing students' performance in assessing patients' health status. Data was analyzed using descriptive statistics methods, independent t-test, and one-way ANOVA by SPSS software. Results: Twenty point four percent of students had a poor performance in assessing patients' health, 68.2% of them achieved moderate score, and only 11.4% were proficient in assessing patients' health. Conclusion: Most senior nursing students were not skillful enough in assessing health status. The collabora-tion of administrators of nursing in ministry of health and medical education, hospitals, nursing schools and instructors in order to make appropriate planning for this problem seems necessary.